2002
DOI: 10.1007/s11745-002-0894-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism and FA composition in tissues of Eurasian perch Perca fluviatilis as influenced by dietary fats

Abstract: Eurasian perch, Perca fluviatilis, were fed a semipurified fat-free diet for 4 wk, followed by a 16% feeding supplementation of either olive oil (OO), safflower oil (SO), linseed oil (LO), or cod liver oil (CLO) as the only lipid source in each diet for 10 wk. Significant reductions in total lipid of tissues were observed (31.4% in viscera, 66.7% in muscle, and 74.1% in liver) after feeding the fat-free diet. The SO-, LO-, and CLO-fed fish significantly increased lipid deposition in liver and viscera compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 51 publications
7
44
0
Order By: Relevance
“…This could have been due to the selective retention of that fatty acid or transformation of fatty acids of the n À 3 family, with a shorter carbon chain and a lower number of double bonds in their long-chain derivatives with a higher degree of unsaturation. The process of bioconversion of n À 3 fatty acids in that species of fish has been confirmed by Xu and Kestemont (2002), as well as by Xu, Fontaine, Mélard, and Kestemont (2001) using reared perch fed a diet with the addition of various vegetable oils and a diet with various contents of fat. These authors point to the high activity of desaturases D5 and D6 in fish of that species and to 18:3 n À 3 as a preferred reaction substrate.…”
Section: Discussionmentioning
confidence: 75%
“…This could have been due to the selective retention of that fatty acid or transformation of fatty acids of the n À 3 family, with a shorter carbon chain and a lower number of double bonds in their long-chain derivatives with a higher degree of unsaturation. The process of bioconversion of n À 3 fatty acids in that species of fish has been confirmed by Xu and Kestemont (2002), as well as by Xu, Fontaine, Mélard, and Kestemont (2001) using reared perch fed a diet with the addition of various vegetable oils and a diet with various contents of fat. These authors point to the high activity of desaturases D5 and D6 in fish of that species and to 18:3 n À 3 as a preferred reaction substrate.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, no significant differences were observed in the content of n-3 PUFA between wild and farmed yellow perch (Gonzalez et al, 2006). Xu and Kestemont (2002) noted that although Eurasian perch contains relatively low fat in muscles, it is a potential nutritional food fish for human consumption as it has a high content of DHA. The results of the above authors indicate that the high tissue DHA content in the muscles of Eurasian perch was attributable to the greater ability for n-3 acid bioconversion.…”
Section: Discussionmentioning
confidence: 93%
“…The same authors also noted, that freshwater fish such as salmonids and common carp fed on diets containing high amounts of fish oil resulted in marketable fish with substantial levels of n-3 PUFA. The literature showed that perch fed on different diets had more EPA and DHA in muscles than AA and LA (Xu and Kestemont, 2002). They also consistently had more n-3 PUFA than n-6 PUFA (Orban et al, 2007, Blanchard et al, 2005, Blanchard et al, 2008, Łuczyńska et al, 2008, Jankowska et al, 2010, Hossain et al, 2011.…”
Section: Discussionmentioning
confidence: 98%
“…Studies carried out on juvenile Eurasian perch (2.9 g initial body weight) or yellow perch (51 g initial body weight) indicate that low dietary fat (10%) and high protein content (>40%) seem to be beneficial for growth performance of percids (Fiogbé et al 1996;Brown et al 1996;Kestemont et al 2001;Xu and Kestemont 2002). Furthermore, increasing lipid tissue incorporation and peritoneal deposition observed in percids indicate low utilisation of dietary lipid supply.…”
Section: Introductionmentioning
confidence: 99%